ANALISIS PELAKSANAAN PROGRAM PENGALAMAN LAPANGAN (PPL) MAHASISWA PROGRAM STUDI PENDIDIKAN GURU PAUD FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU TAHUN AKADEMIK 2014/2015 - Ema Gusnimar; Wilson '; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:. The aim of this research is to know the implementation of Field Experience Program (PPL) of early childhood education study program faculty of teacher training and education riau university academic year 2014/2015. The subject of this research is the students of early childhood education study program faculty of teacher training and education riau university academic year 2014/2015consisting of 42 Students. In accordance with qualitative research approach then in this research data collection techniques used are interviews, observation and documentation. While the data analysis technique used is qualitative analysis according to Miles and Huberman (Sugiono, 2011) has 3 stages namely 1) data reduction, 2) presentation of data, 3) draw conclusions and verification. In this study, researchers seek an extension of participation and keajegan to gain confidence and establish intimacy with the speakers. Researchers also use triangulation method by digging information using different methods, namely matching the data obtained through interviews, observation, and documentation. The results of this study indicate that the implementation of field experience program (PPL) students study program of teachers PAUD FKIP University of Riau in doing done gradually starting from observation, teaching exercises, to making reports PPL results. Implementation of PPL is guided by teachers pamong, lecturers PPL supervisor and head of the school where the PPL. Overall the implementation of PPL runs smoothly although there are some activities both at the observation stage, teaching exercises and at the reporting stage that is not in accordance with the guidance of PPL FKIP University of Riau implementation related to PPL students, teachers, lecturers and PPL from PPL schools.Keywords: Implementation, Field Experience Program (PPL)